Marketplace Responsibility for the Distribution of Counterfeit Flavoring Products: A Maqasid al-Shariah Perspective - Alifah Nahdah; Rahmat Hidayat (LP2M IAIN Palopo, 2026)
The development of marketplaces has facilitated digital transactions; however, it has also increased the circulation of counterfeit flavoring products that potentially cause economic and health-related harm to consumers. This study aims to analyze marketplace responsibility for the distribution of such products and to examine it from the perspective of maqashid al-shariah. The legal research method employed in this study is a normative-empirical legal approach, with data collected through literature review and observation of the sales practices of counterfeit flavoring products in marketplaces. The data were analyzed qualitatively through normative interpretation, comparison between legal norms and actual practices, and evaluation based on the principles of maqashid al-shariah. The findings indicate that marketplace supervision remains reactive and has not been optimally implemented in a preventive manner, thereby allowing the widespread circulation of counterfeit products. From the perspective of maqashid al-shariah, marketplace responsibility is not merely formal as a platform provider, but also encompasses an active obligation to prevent harm, protect consumer welfare, and ensure justice in digital transactions. This responsibility is closely related to the protection of life (hifz al-nafs), the protection of property (hifz al-mal), and the protection of lineage (hifz al-nasl). Therefore, marketplace operators bear both ethical and legal responsibilities to implement preventive supervision, seller verification, product control mechanisms, and consumer protection measures as part of realizing the objectives of Sharia in digital economic activities